South Sudan’s Infrastructure : A Continental Perspective - Ranganathan, Rupa; Briceno-Garmendia, Cecilia M. (2012)
Newly independent South Sudan faces a challenge in making its own way in infrastructure development. Despite earning $6 billion in oil revenues since 2005, South Sudan's spending has not been proportional to its income, but rather has lagged behind North Sudan's development of infrastructure and social support. South Sudan benefitted from strong donor support during 2004-10, the interim period defined by the Comprehensive Peace Agreement. It focused on reestablishing regional transport links and access to seaports as well as rehabilitating its ports, airstrips, and single rail line. South Sudan also successfully liberalized the ICT sector. Nonetheless, the new country's infrastructure remains in such a dismal state that it is difficult to pinpoint a single most pressing challenge. The transport sector accounts for half of the country's spending needs, and water and sanitation account for a further quarter of the total. But so many improvements are needed that the nation cannot realistically catch up with its neighbors within 10 years, or even longer. South Sudan's annual infrastructure funding gap is $879 million per year. Given that the country's total needs are beyond its reach in the medium term, it must adopt firm priorities for its infrastructure spending. It also must attract international and private-sector investment and look to lower-cost technologies to begin to close its funding gap. Although South Sudan loses relatively little to inefficiencies, redressing those inefficiencies will be vital to creating solid institutions to attract new investors and get the most out of their investments.